Unique Finding of a Primary Central Nervous System Neuroendocrine Carcinoma in a 5-Year-Old Child: A Case Report - Stepien, Natalia; Haberler, Christine; Theurer, Sarah; Schmook, Maria-Theresa; Lütgendorf-Caucig, Carola; Müllauer, Leonhard; Gojo, Johannes; Azizi, Amedeo A.; Czech, Thomas; Slavc, Irene; Peyrl, Andreas (Frontiers in Neuroscience, 2022)
Neuroendocrine tumors (NETs) are rare neoplasms predominantly arising in the gastrointestinal-tract or the lungs of adults. To date, only ten cases of primary central nervous system (CNS) NETs have been reported, with just three of them describing a neuroendocrine carcinoma (NEC) and none occurring in a child. We report on a previously healthy 5-year-old boy, who presented with headaches, nausea and vomiting, and was diagnosed with a left cerebellar solid mass with a cystic component. After gross-total resection, histology revealed a neuroendocrine carcinoma. Molecular analysis of the tumor tissue showed a KRAS-splice-site mutation (c451-3C>T). The KRAS-mutation was discovered to be a maternal germline mutation, previously described as likely benign. After extensive search for an extracranial primary tumor, including Ga-68 DOTANOC-PET-CT, the diagnosis of a primary CNS NEC was established, and proton irradiation was performed. Unfortunately, the patient developed an in-field recurrence just five weeks after the end of radiotherapy. The tumor was re-resected with vital tumor tissue. Six cycles of chemotherapy were initiated, consisting of cisplatin, carboplatin, etoposide and ifosfamide. The patient remains disease free 18 months after the end of treatment, supporting the beneficial effect of platinum- and etoposide-based chemotherapy for this tumor entity.